A case report of retiform hemangioendothelioma as pleural nodules with literature review. Issue 1 (December 2015) - Liu, Qingqing; Ouyang, Ruoyun; Chen, Ping; Zhou, Rui
Abstract Retiform hemangioendothelioma (RH) is a rare low-grade variant of angiosarcoma mostly reported on dermis or subcutaneously. A 30-year-old woman suffering from dry cough, dyspnea and pleural effusion has been described. Distinctive symptoms and lesions on high resolution computed tomography (HRCT) scan and common histological, immunological feature are discussed. Diagnosis was made by thoracoscopy as RH.